Synthesis Chitosan nanoparticles from Animal Byproducts (Shrimp Shells) Characterization, Physical Properties and Toxicity of Polymeric Nanoparticles in vivo - Kadhim H. Abdul Sayed; Alaa G. Al-Hasimi; kareema M. Ziadan (Kufa Journal for Agricultural Sciences)
The study included the extraction of Chitin (Ch) from shrimp shells and preparation of Chitin nanoparticles (NCh) using acid hydrolysis and ultrasound method. In addition, the preparation of chitosan (Chs) and Chitosan nanoparticles (NChs) by Deacetylation method, then we study some of the characteristics, including yield, diameter by Size Analyzer, Field Emission Scanning Electron Microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy, X-Ray Diffractometer (X-RD), Viscosity, Water Binding Capacity (WBC) and Fat Binding Capacity (FBC). The results showed, (a) decreased the percentage of yield of NChs to 8.20%, (b) the effective diameter of the natural chitosan using a Size Analyzer and was 28121.5 nm, (c) FESEM analysis revealed that the NChs displayed a nanoscale structure with diameters ranged from 20.93 - 30.20 nm (d) the degree of deacetylation (DD%) using FT-IR spectroscopy device, of NChs was (80.21%) compared to Chs 71.45%, and in addition, from the X-ray spectrum, two peaks in spectra of (Ch, NCh) and (Chs, NChs) were observed at the diffraction angles (2θ) which are (10.70-10.99) and (19.99-20.37). Results show increasing the crystallization coefficient of NCh and NChs, while viscosity, WBC and FBC of NChs decreased compared to Chs. The NChs did not show any toxic effect on human blood cells at concentrations of 100-1000 µg. ml-1.